(untitled) (Research, Society and Development, 2024)
The article addresses the importance of female inclusion in the technology sector, highlighting that this inclusion is a matter of equity and a crucial factor for innovation and economic development. This study aimed to analyze the representation of women in technology and the barriers they face, such as underrepresentation in leadership positions and wage inequality. The methodology used is integrative bibliographic research, which reviews data and literature on the presence of women in the sector between 2015 and 2022. The results show that only 26% of the technology workforce in Brazil is composed of women, with only 18% occupying leadership positions. This reality highlights the urgent need for initiatives that promote female inclusion and empowerment, aiming to increase diversity and representation in this field. The study emphasizes that gender inequality persists at an alarming rate, especially in fields of science, technology, engineering, and mathematics (STEM). Female inclusion is presented not as a moral imperative but as a necessary condition for economic and social progress. Initiatives such as mentoring programs are essential to creating a more inclusive environment. Recognizing and valuing the contributions of women in technology is important for a more innovative and sustainable future, emphasizing the phrase “A woman’s place is wherever she wants it to be!” as a symbol of the fight for equality and inclusion.